PENERAPAN PROGRAM BINA LINGKUNGAN BADAN USAHA MILIK NEGARA BERBASIS PEMBERDAYAAN MASYARAKAT PADA ANGKASA PURA INDONESIA CABANG SOEKARNO HATTA: Implementation of State Owned Enterprises Community Development Program Based on Community Empowerment at Angkasa Pura Indonesia Soekarno Hatta - Irindita Tiarasari; Sri Bakti Yunari (Faculty of Law, Universitas Trisakti, 2025)
The community development program, as part of the Partnership and Community Development Program (PKBL), represents one of the SOE’s contributions, aiming to empower and enhance the quality welfare of the surrounding community. This program is an implementation of Article 88 of Law Number 19/2003 about State-Owned Enterprises. The research problem is how the community development program based on community empowerment is implemented by PT Angkasa Pura Indonesia Soekarno Hatta Airport Branch Office. This following research applies normative juridical research type with descriptive research nature. The data utilized include secondary data supported by primary data, obtained through literature studies and interviews. The analysis is conducted qualitatively to evaluate the programs implementation includes the challenges encountered, and its impact on the community, with conclusions drawn deductively. The research findings that the implementation of the program has been reasonably effective thus far. However, there are challenges, including dissatisfaction among the community regarding the assistance provided. Nonetheless, the program's impact has yielded positive effects for both the community and the company.